An Overview on Diabetis Mellitus - Jangid, Hrishabh; Chaturvedi, Saurabh; Khinchi, M. P. (Asian Journal of Pharmaceutical Research and Development, 2017)
Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. Diabetes is due to either the pancreas not producing enough insulin or the cells of the body not responding properly to the insulin produced. Symptoms of marked hyperglycemia include polyuria, polydipsia, weight loss, sometimes with polyphagia, and blurred vision. Diabetes is a more variable disease than once thought and people may have combinations of forms. There is no known preventive measure for type 1 diabetes. Type 2 diabetes, which accounts for 85-90% of all cases - can often be prevented or delayed by maintaining a normal body weight, engaging in physical exercise, and consuming a healthful diet. Type 1 diabetes can only be treated with insulin, typically with a combination of regular and NPH insulin, or synthetic insulin analogs. Metformin is generally recommended as a first line treatment for type 2 diabetes, as there is good evidence that it decreases mortality.